2015
DOI: 10.1080/02791072.2015.1094590
|View full text |Cite
|
Sign up to set email alerts
|

Ayahuasca Tourism: Participants in Shamanic Rituals and their Personality Styles, Motivation, Benefits and Risks

Abstract: Ayahuasca continues to attract tourists to South America, where there has been a growth in the number of centers offering hallucinogenic ayahuasca experiences. The aims of this study were to (1) discover the reasons foreigners seek this type of experience; (2) define what an ayahuasca experience entails; (3) discover subjective perceptions of ayahuasca's benefits and risks; and (4) describe personality styles of participants using the personality questionnaire (PSSI). Participants (N=77) were persons who had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 21 publications
5
70
0
9
Order By: Relevance
“…The Mini-International Neuropsychiatric Interview (MINI) interview showed that 45% of the sample met the diagnostic criteria for a psychiatric disorder. This finding is in line with the main reasons reported by participants for attending ayahuasca ceremonies, which include the treatment of mental health problems and to achieve psychological well-being 27,31,32 . Remarkably, at the 1-month follow-up, 61% of participants who initially met the www.nature.com/scientificreports www.nature.com/scientificreports/ diagnostic criteria no longer met the criteria for any psychiatric disorder.…”
Section: Discussionsupporting
confidence: 87%
“…The Mini-International Neuropsychiatric Interview (MINI) interview showed that 45% of the sample met the diagnostic criteria for a psychiatric disorder. This finding is in line with the main reasons reported by participants for attending ayahuasca ceremonies, which include the treatment of mental health problems and to achieve psychological well-being 27,31,32 . Remarkably, at the 1-month follow-up, 61% of participants who initially met the www.nature.com/scientificreports www.nature.com/scientificreports/ diagnostic criteria no longer met the criteria for any psychiatric disorder.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding "Values", the other psychological process variable studied here, there are many personal reports from ayahuasca users referring to the ayahuasca experiences as transformative ones that can be manifested as changes in personal values (Kavenská and Simonová, 2015). Previous studies found selfreported changes in life attitudes and changes in personal values and life meaning after the administration of different doses of psilocybin (Griffiths et al, 2008;Griffiths et al, 2011), and differences in life purpose and related variables in long-term ayahuasca users (Barbosa et al, 2016;Bouso et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Hallucinogen use is considered a core element of relatively well-structured religions, such as the Brazilian Amazon Santo Daime Church. Interest on the beneficial psychic effects of ayahuasca is actually increasing in Europe and North America, as are reports of intoxication from the drug 29,30 . Also, a naive belief in "scientifically supported" information, especially among internet fans, and a persistent interest in mystic theories such as the third eye, may contribute to creating a favorable scenario that increasingly incites people to…”
Section: Final Remarksmentioning
confidence: 99%